Xác định nhóm chỉ thị sinh hóa sulhydryl (-SH) cho sự ô nhiễm asen và đồng của cây rau má (Centella asiatica) - Khoa và cộng sự, Nguyễn Cửu (Vietnam Journal of Chemistry, 2014)
Plants can produce Cys-rich peptides such as triptide or glutathione (GSH), polypeptide, etc. when exposed to an excess amount of heavy metals. These peptides are rapidly synthesized in response to toxic levels of heavy metals in all tested plants. Amount of (-SH) groups indicated the level of contamination. Total (-SH) groups in pennywort were quantitated with Ellman’s reagent by spectrophotometer in absorbance at 412nm. Arsenic, copper-peptide complexes were identified by HPLC with a Phenomenex Ultracarb 7ODS30 (250mm´4.6 mm i.d.´10 mm) column, mobile phase A: 40% H2O, B: 40% acid formic 2.5% and C: 20% methanol; detector Diod Array UV at 275 nm. The results showed that uptaken and accumulation an excess amount of As, Cu is caused increasing indicator (-SH) groups in pennywort. This indicated that pennywort is very sensitive to As and Cu in terms of the rapid increases in the levels of GSH.